Improvement on Student LearniInterest through the Integrated Sciences Learning Based on Webbed Model - Mulyani Mulyani; Wan Syafii; L.N. Firdaus (Universitas Riau, 2020)
This study aims to determine differences in increasing student interest in the learning process through integrated science learning based on Webbed Model. The basis of this research was the students low interest in the learning process as a result of the implementation in natural science learning that is not in accordance with the mandate of the 2013 curriculum. The research method was a quasi-experiment with a randomized pretest-posttest control group design. Data collection techniques were questionnaires for students interest in learning based on predetermined indicators. While data analysis techniques, which were in the form of descriptive analysis and statistical analysis, were using the Independent Sample T Test. The results showed that an increase in student interest in learning through integrated science-based Webbed Models by 2.9% with a very good category. Furthermore, based on statistical tests the fcount is 10.813 > ftabel 0.40 and 0.315 was obtained with a significance value of 0.04. Thus, it can be concluded that there are some differences in student interest in learning through integrated Webbed Model-based science learning.